2021
DOI: 10.1128/mbio.00129-21
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Metabolically Quiescent Leishmania mexicana Parasites in Peripheral and Cured Dermal Granulomas Using Stable Isotope Tracing Imaging Mass Spectrometry

Abstract: Leishmania are sandfly-transmitted protists that induce granulomatous lesions in their mammalian host. Although infected host cells in these tissues can exist in different activation states, the extent to which intracellular parasites stages also exist in different growth or physiological states remains poorly defined. Here, we have mapped the spatial distribution of metabolically quiescent and active subpopulations of Leishmania mexicana in dermal granulomas in susceptible BALB/c mice, using in vivo heavy wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…A recent study by Kloehn et al. ( 41 ) showed unique lipids distributed across the lesion induced by L. mexicana and surrounding host tissue. However, to our knowledge, there is no evidence that highlights lipid compositional changes between inflammatory microenvironments at different time points of infection.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…A recent study by Kloehn et al. ( 41 ) showed unique lipids distributed across the lesion induced by L. mexicana and surrounding host tissue. However, to our knowledge, there is no evidence that highlights lipid compositional changes between inflammatory microenvironments at different time points of infection.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier research demonstrated the ability of MSI to visualize candidate peptides derived from visceralising Leishmania in mice (55) and to relate peptides to cutaneous Leishmania infection in mice (56). A recent study by Kloehn et al (41) showed unique lipids distributed across the lesion induced by L. mexicana and surrounding host tissue. However, to our knowledge, there is no evidence that highlights lipid compositional changes between inflammatory microenvironments at different time points of infection.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations